2022
DOI: 10.1097/mog.0000000000000895
|View full text |Cite
|
Sign up to set email alerts
|

Point of care diagnostics for Cryptosporidium: new and emerging technologies

Abstract: Purpose of reviewAlthough Cryptosporidium detection and typing techniques have improved dramatically in recent years, relatively little research has been conducted on point of care (POC) detection and typing tools. Therefore, the main purpose of the present review is to summarize and evaluate recent and emerging POC diagnostic methods for Cryptosporidium spp. Recent findingsMicroscopy techniques such as light-emitting diode fluorescence microscopy with auramine-phenol staining (LED-AP), still have utility for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have demonstrated that the combination of RPA and CRISPR-Cas-based detection systems can improve detection sensitivity and specificity (Hijjawi et al 2023 ). We then tried to employ RPA in the CRISPR-Cas12b-based detection systems to enhance the efficacy of the systems for mcr-1 and tet (X4) detection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that the combination of RPA and CRISPR-Cas-based detection systems can improve detection sensitivity and specificity (Hijjawi et al 2023 ). We then tried to employ RPA in the CRISPR-Cas12b-based detection systems to enhance the efficacy of the systems for mcr-1 and tet (X4) detection.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the CRISPR-Cas system can be combined with isothermal amplification methods, such as RPA, which offer the advantages of simplicity and rapidity, to further enhance the specificity and sensitivity of detection (Hijjawi et al 2023 ; Li et al 2022a , b , c , d , e ). However, this approach involves nucleic acid amplification before detection using the CRISPR-Cas system, which may result in aerosol contamination (Lin et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptosporidium, a single-celled parasite, has broad host specificity [1]. Cryptosporidium parvum is the most common infectious species, particularly in neonates and/or young ruminants [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, INAs have some limitations, e.g. low precision and restrictions in multiplex detection (8)(9)(10)(11)(12)(13). Nevertheless, the ease of use of INAs provides a valuable diagnostic tool for pandemic response.…”
Section: Introductionmentioning
confidence: 99%